Pengembangan Potensi Desa Wisata di Kabupaten Ciamis : Menuju Ekowisata Berkelanjutan di Desa Winduraja - Mochamad Alfiansyah; Muhammad Fariz; Resti Illa Rahayu; Syiffa Putri Z.S (Jurnal Hukum dan Sosial Politik, 2025)
Research activities with the theme "Development of Tourism Village Potential in Ciamis Regency" were carried out by students of the FISIP Government Science Study Program at Galuh University involving 10 students. This program aims to analyze social phenomena and the potential of human and natural resources in government administration. This activity involves lecturers, village staff, the people of Winduraja Village, Kawali District, and students in various activities, such as sustainable ecotourism training. The methods used include an initial survey to identify village potential, observation, interviews, documentation and ongoing assistance. The results of the activity show that the people of Winduraja Village are starting to have awareness and understanding of the tourism potential of Situ Wangi. This program is expected to increase community readiness to manage and promote Winduraja Village as a competitive tourist destination. Sustainability of this program requires joint commitment and support from the government and related institutions.